The utilization of leguminous Gliricidia sepium as natural fertilizers to improve soil fertility - Aroonluk, S.; Prasertkul, T.; Tongchure, S.; Phitchayapon, C.; Talubnak, C. (International Journal of Agricultural Technology, 2020)
Soil degradation is one of the most important problem to be solved for sustainable agriculture. To improve soil from repetitive land use, the leguminous plant Gliricidia sepium was evaluated as natural fertilizer supplementation. The experiment was carried out in pot trial. Green leaf manure and intercropping gave positive effects on the growth of sweet corn. The pH, organic matter content as well as nitrogen, potassium, phosphorous and calcium content of the soil amended with the leaves of G. sepium increased. Green leaf manure at 5 and 10 percent supplementation gave the highest plant growth at 4 weeks after transplantation. However, 10 and 20 percent supplementation ratio gave the highest plant development at 8 weeks after transplantation. The chemical properties and nutritional status of the soil increased when mixed with green manure or intercropped with G. sepium.